Gli intercalari: appoggi della mente o parassiti del linguaggio: dinamiche segrete in quello che si ripete involontariamente (PHRASIS | Rivista di studi fraseologici e paremiologici, 2017)
The aim of this paper is to offer a survey on a particular kind of saying, a not very well studied topic. The topic is studied under different perspectives, taking into account litterature, history, old anecdotes, up to current times and modern mass media. The presence of sayings is analyzed with a series of examples (from classical Greek and Latin auctores up to scenes and stories from everyday life). The purpose is to give an idea of the often overlooked diffusion of these «support of the mind or parasites of the language » and of the range of implications linguistic, cultural and psychological ones that hides in secret and unintentional dynamics of repetition.
Keywords: Sayings, litterature, history, poli- tics, psychology